Pay dirt eaudiobook - Paretsky, Sara (V. I. Warshawski, 2024)
Legendary detective V.I. Warshawski uncovers a mystery with roots dating back to the Civil War in this edge-of-your-seat thriller from New York Times bestseller Sara Paretsky. V .I. Warshawski is famous for her cool under fire, her intelligence, her humor, her unflinching courage, and her love of good coffee. But even the strongest people sometimes need a break to recharge, so her friends send her to Kansas for a weekend of college basketball where Angela, one of her protégées, is playing. And that's where trouble finds V.I. Sabrina, one of Angela's roommates, disappears and V.I. agrees to try to find her. Finding a missing person in a city where she knows few people and doesn't have her trusted contacts is hard, but not as hard as the brutally negative reaction to the detective from some of the locals. When V.I. finds Sabrina close to death in a remote house, she lands herself in the FBI's crosshairs and faces a violent online backlash. The men running the county's opioid distribution are also not happy. Discovering a dead body in the same house a few days later, V.I. is pitched headlong into a local land-use battle with roots going back to the Civil War. She finds that today's combatants are just as willing as opponents in the 1860s to kill to settle their differences. V.I.'s survival depends on keeping one step ahead of players in a game she never intended to play, before the clock runs down.